Widespread introgression in Chinese indigenous chicken breeds from commercial broiler. (22nd January 2019) - Zhang, Chunyuan; Lin, Deng; Wang, Yuzhe; Peng, Dezhi; Li, Huifang; Fei, Jing; Chen, Kuanwei; Yang, Ning; Hu, Xiaoxiang; Zhao, Yiqiang; Li, Ning
Abstract: Chinese indigenous chickens (CICs) constitute world‐renowned genetic resources due to their excellent traits, including early puberty, good meat quality and strong resistance to disease. Unfortunately, the introduction of a large number of commercial chickens in the past two decades has had an adverse effect on CICs. Using the chicken 60 K single nucleotide polymorphism chip, we assessed the genetic diversity and population structure of 1, 187 chickens, representing eight Chinese indigenous chicken breeds, two hybrid chicken breeds, two ancestral chicken breeds, two commercial populations and additional red jungle fowl. By investigating haplotype similarity, we found extensive gene introgression from commercial broiler to almost all CICs. Approximately 15% of the genome, on average, of CICs was introgressed, ranging from 0.64% for Tibetan chicken to 21.52% for Huiyang Bearded chicken. Further analysis revealed signals consistent with positive selection in the introgression loci. For the first time, we systematically mapped and quantified introgression from commercial broiler to CICs at the whole genome level. Our data provided a usable resource for chicken genetic diversity, and our findings indicated a dire need for protecting the genetic resources of CICs.